INTELLECTUAL CAPITAL DALAM MENINGKATKAN DAYA SAING: SEBUAH TELAAH LITERATUR - Noorina Hartati (ETIKONOMI, 2014)
Intellectual Capital becomes an interesting topic to discuss and to research because it provides more value for the company thereby increasing competitiveness. Therefore, it should be realized by the owners or top management that the training programs to improve employee competency needs to be improved rather than just buying land for business expansion and new machinery. Based on the research from experts proves that companies that have a more intellectual capital than its competitors the company more profitable, as well as financial performance and firm value better. Viewed from the standpoint of accounting, disclosure of intellectual capital can be seen from the financial reporting of the company through good training programs and human resource spending can increase employee competency, so that the impact effect on Free Cash Flow (FCF) is risingDOI: 10.15408/etk.v13i1.1878